1980
DOI: 10.1007/bf00558453
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of intravenous and oral sulpiride in healthy human subjects

Abstract: The pharmacokinetics of sulpiride was studied in 6 healthy volunteers after intravenous and oral (tablets) administration of 100 mg. An open two- and in two subjects a three-compartment model was applied following intravenous administration. The average total distribution volume during the terminal slope was 2.72 +/- 0.66 l/kg and total systemic clearance was 415 +/- 84 ml/min. The serum half-life of the terminal slope following intravenous administration averaged 5.3 h (range 3.7--7.1 h) according to the two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 6 publications
10
57
0
5
Order By: Relevance
“…The obtained results showed that the bioavailability after oral sulpiride SD administration was approximately 180% relative to the corresponding raw sulpiride suspension, an encouraging finding considering the reported 27-30% oral bioavailability after oral administration of sulpiride solution to humans (9,23). Tartaric acid as a hydrophilic carrier for SD development offers various advantages such as low toxicity, high compatibility, high water solubility, and low cost (24), which complied with the desired target product profile.…”
Section: Development and Optimization Of Sulpiride Sd-loaded Suppositmentioning
confidence: 55%
See 1 more Smart Citation
“…The obtained results showed that the bioavailability after oral sulpiride SD administration was approximately 180% relative to the corresponding raw sulpiride suspension, an encouraging finding considering the reported 27-30% oral bioavailability after oral administration of sulpiride solution to humans (9,23). Tartaric acid as a hydrophilic carrier for SD development offers various advantages such as low toxicity, high compatibility, high water solubility, and low cost (24), which complied with the desired target product profile.…”
Section: Development and Optimization Of Sulpiride Sd-loaded Suppositmentioning
confidence: 55%
“…Following intravenous bolus dosing, sulpiride showed a distribution volume of 2.7 L/kg and a prolonged half-life of 11-14 h and was considered to be convenient for once-daily administration. Sulpiride showed slow and incomplete absorption from the gastrointestinal tract with a bioavailability not exceeding 27% (9). Moreover, it is worth noting that there are no rectal products of sulpiride in the market and scarce information exists on its rectal availability.…”
Section: Introductionmentioning
confidence: 99%
“…The maximal plasma concentrations after oral administration of 50 mg amisulpride or 100 mg sulpiride are 0.13 and 0.29 μM, respectively (48,49). These values are much lower than the K M for the uptake of amisulpride and sulpiride by the transporters studied ( Table I), meaning that transport in vivo will not be saturated.…”
Section: Discussionmentioning
confidence: 75%
“…6,7) After oral administration of 100-400 mg in humans, peak plasma levels of 0.2-1.5 mg/ml are obtained within 1-3 h, and the elimination half life is 7-8 h. [8][9][10] After intravenous administration of sulpiride, 70% of the dose is recovered as unchanged drug in urine, as compared to 15% after oral administration, 11) and the bioavailability of the oral form is 25-36%. 10,11) After oral dosing of 14 C-labeled sulpiride, urinary excretion of radioactivity was 27-52%, and more than 95% of the radioactivity recovered in the urine and feces is unchanged sulpiride. 8) It has been reported that sulpiride is coadministered with other drugs including olanzapine, 12,13) fluvoxamine, 14) and cimetidine 15) for the treatment of schizophrenia, depression, and gastro-duodenal ulcers, respectively.…”
mentioning
confidence: 99%